A city-wide survey of dental students' opinions on undergraduate oral surgery teaching - GÖNÜL, ONUR (WILEY, 2020)
Purpose This study aimed to carry out a city-wide survey to evaluate undergraduate students' opinions on their oral surgery training by measuring their self-confidence. Materials and Methods A cross-sectional survey of 383 3rd year, 412 4th year and 363 5th year undergraduate dental students from six dental schools in Istanbul with a mean age of 22.73 +/- 1.55 was conducted towards the end of the academic year. A web link to the questionnaire was sent to the contact person at the participating dental schools. The questionnaires were anonymously evaluated. Descriptive statistics were calculated, and Chi-square tests were performed to examine the data. A P-value of In total, 1158 responses were returned, representing 67% of the overall students in the 2018-2019 academic year. The male respondents were significantly more self-confident than females in the general aspects of surgical skills. More than half of the respondents (53%) felt confident in oral surgery knowledge to undertake independent practice. Although 5th year respondents felt more confident in the general aspect of the questionnaire, their ability of differentiation of odontogenic and non-odontogenic pain was lower than their counterparts. The majority (86%) of the participants disagreed that the only knowledge required for oral surgery was that of tooth and jaw anatomy. Conclusion This survey revealed perceived confidence in tooth and retained root extraction. The male respondents were found to be more self-confident. There is a need for improvement in surgical skills, recognition of malignancies and differentiation of the origin of the pain.
Keywords: anatomical knowledge; dental students' opinion; oral surgery teaching; self-confidence; EXPERIENCE; PRACTITIONERS; CONFIDENCE; COMPETENCE; SCHOOL